ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN KENDARAAN PADA PT XYZ: ANALISIS SISTEM PENGENDALIAN INTERNAL PERSEDIAAN KENDARAAN PADA PT XYZ - Pipin Fitriasari (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2026)
This research aims to find out how internal control is one of the methods used to anticipate fraud and anticipate the possibility of uncollectible receivables, with the existence of control it can minimize losses caused by bad debts. Apart from that, it also explains how an Internal Control System is needed in processing so that errors do not occur in managing data from the warehouse to the dealer. Like the problem experienced by the company XYZ, namely an error in reporting inventory from the warehouse to the head office. This problem can make the Stock Report for Management not match the physical condition. With this type of qualitative research and with a descriptive approach, with the qualitative approach chosen in this research, the researcher hopes that it will provide more space for researchers in describing how effective internal control is in the company vehicle inventory. Data collection techniques in this research were carried out using observation, interviews and documentation, so that the research results could be concluded by the company XYZ already has Internal Control in place, however there is still weak supervision and safeguarding of several employees. And there are still employees who do not follow the SOP for picking up units, if there is no good stock control there will be losses in the future. Organizational structure at the company has been running well in accordance with the duties and responsibilities of each employee, however there are some employees who do double work. Management control carried out by the company only checks if discrepancies occur. The risk that occurs in controlling inventory management is disputes or even loss.